Le révisionnisme allemand en assaut - Derlatka, Tadeusz; Nurowski, Roman; Lesniewski, Andrzej (Poznan: Wydawnictwo Zachodnie; Warszawa, 1960)
"Tadeusz Derlatka, Roman Nurowski, Andrzej Lesnieuwski Bibliotheek Camille Huysmans"